Threat to sustainable environments: reappraisal of cases and causes of building failures in nigeria (2015)
It is a common sight recently in the developing countries especially in Nigeria to find buildings collapsing in cities and towns. Such buildings cut across several use and function (private, corporate, religious and public), exposing innocent lives to harm and unwarranted death. This paper considers the various reasons, causes and factors at the root of this menace affecting building and sustainable environment. Some of the causes were traced back to the planning and conceptual design stages before the actual construction of the building takes place. The paper argues that the problem of building collapse and disaster is not due to lack of knowledge of its causes but in ensuring that such probable factors were programmed not to happen. This with involve putting in place, appropriate precautions from the design stage to ensure the durability, sustainability and functionality of the building through careful construction process and good maintenance.